Odprta znanost in avtorske pravice - Fidler, Ana (Knjižnica, 2024)
One of the fundamental principles of open science is open access to the results of publicly funded research. Authors or copyright holders ensure open access, among other things, through appropriate copyright management. The governing law for copyright in Slovenia is the Copyright and Related Rights Act, which was last amended in September 2022. The amendment introduced two important exceptions for open science in Slovenia: an exception for text and data mining for scientific research and a general exception for scientific research. In November 2021, the Scientific Research and Innovation Activities Act was adopted. In May 2023, the Decree on the Implementation of Scientific Research Work in accordance with the Principles of Open Science was adopted. These two legal acts specify the provision of open access to all peer-reviewed scientific publications, research data and other research results in the context of research, co-funded by public resources at a minimum of 50%. In this article, we describe in more detail the copyright legislation in Slovenia and the changes in the field of open science. We present Creative Commons licenses, which are world-renowned and important for better accessibility to research results, knowledge dissemination and education quality. We will also introduce the Rights Retention Strategy and the Secondary Publication Right as measures and initiatives developed to promote access to and reuse of publications and address the limitations that copyright legislation represents for research.
Keywords: avtorske pravice; copyright; odprta znanost; odprte licence; open licenses; open science; pravica do sekundarnega publiciranja; rights retention strategy; secondary publishing right; strategija ohranjanja pravic